Step it up and go the story of North Carolina popular music, from Blind Boy Fuller and Doc Watson to Nina Simone and Superchunk - Menconi, David Lawrence (University of North Carolina Press, 2020)
"This book is a love letter to North Carolina's popular music in all its many-splendored glory, from bluegrass, folk, and country to R & B, rock, and pop. Though the state's diverse music scenes have often operated in the shadows of better-known hubs for popular genres-New York, Los Angeles, Detroit, Nashville, Austin, and Athens, Georgia-David Menconi shows North Carolina's influence on American popular music runs deep. He uses profiles of artists and their role in creating or shaping genres to reveal the richness of the state's musical landscape, with an arc that runs from the origin of recorded music in the state to the digital age"--
Keywords: Geschichte; Unterhaltungsmusik; Unterhaltungsmusiker; North Carolina; Popular music / North Carolina / History and criticism; Musicians / North Carolina; Musicians; Popular music; Criticism, interpretation, etc